An Investigation on android background services for controlling the unauthorized accesses using android LOG system - Kotecha, Jay; P, Prabu (International Journal of Engineering and Technology, 2018)
In the current world of technology, people are updating to smart devices day by day. Users often keep personal information on their smartphones, but it increases the threat to the privacy of their data. There are many applications which require the user data to provide specific services such as WhatsApp, Instagram, Paytm, PhonePe, etc., There are special permissions which can be misused by some applications, like READ_EXTERNAL_STORAGE, READ_SMS, SEND_SMS, WRITE_EXTERNAL_STORAGE, READ_CONTACTS, etc., Many applications take users data to their servers without the knowledge of user by running in the background. In this paper, it is shown that how an application runs in the background by running various services, and performs the background activities like notifications, displaying ads, etc., A proposed algorithm is described that how every activity of the background services can be monitored using Android Log and user can be alerted by showing which data is being accessed by the particular application.Â